The Effect of Using STEAM Approach on Developing Computational Thinking Skills among High School Students in Jordan - Al-Haj Bedar, Rana; Al-Shboul, Muhannad Anwar (International Journal of Interactive Mobile Technologies (iJIM), 2020)
The growing demand for combining digital technology with learning practices has surpassed the use of technology or learning how to use it into the process of enhancing learners’ intellectual levels and scaffolding their understanding by focusing on skills that include thought processes gathered in what is called computational thinking. On the other hand, educational challenges promote the search for new instructional tools and approaches. Consequently, learning shall be extended by superimposing science, technology, engineering, arts, and mathematics (STEAM) approach in the instructional practices. The aim of this paper is to show how STEAM approach can develop the computational thinking among high school learners in Jordan. The main skills of computational thinking included: algorithmic thinking, abstraction, decomposition, and generalization. The sample of this study involved 32 high school students in a private school in Amman. The experimental group studied geography skills in a STEAM approach that included the use of online resources such as LightBot maze and the Ordnance Survey maps (OS) website. The control group studied the same content but through conventional method. Findings showed a significant development in the computational thinking especially in algorithmic thinking and abstraction. Thus a STEAM approach learning environment is one of the effective methods of teaching that improved computational thinking.